2017
DOI: 10.1111/jftr.12226
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Acceptance–Rejection Theory: Application to Lesbian, Gay, and Bisexual Persons

Abstract: Many researchers have focused on parents' responses to their child's sexual identity. Although this type of research has been conducted over the past 2 decades on the impact of coming out, there is not a consistently implemented theoretical orientation used across lesbian, gay, and bisexual (LGB) literature for describing and understanding the implications of coming out. However, interpersonal acceptance–rejection theory (IPARTheory) can be used as a framework to describe the experiences of acceptance–rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
(174 reference statements)
0
12
0
1
Order By: Relevance
“…Between 2010 reported 86 articles published on LGBT-related issues out of 3,206 articles, a rate (2.68%) that was significantly lower than the rate in MFR between 2010 and 2017 (14/250, 5.6%), with an odds ratio of 2.15 (95% CI, 1.21 to 3.84, p = .01). We also observed that JFTR published at least 15 articles (of 208) between 2009 and 2017 that dealt with LGBT-family research issues, a rate of 7.2%, higher than MFR or the top seven family journals; those articles included 14 reviews or commentaries (Allen, 2016;Berkowitz, 2009;Cao, Mills-Koonce, Wood, & Fine, 2016;Chrisler, 2017;Cohen, 2011;Doucet & Lee, 2014;Few-Demo, Humble, Curran, & Lloyd, 2016;Fuller, 2017;Glennon, 2012;Goldberg, 2013;Lauer & Yodanis, 2010;McGuire, Catalpa, Lacey, & Kuvalanka, 2016;McGuire, Kuvalanka, Catalpa, & Toomey, 2016;Widiss, 2016; as well as one empirical paper (Connidis, 2012), not counting editorials for special issues (e.g., Oswald, 2016). In addition, JFTR also published four articles that tangentially mentioned LGBT issues (Few-Demo, 2014;Galvin & Braithwaite, 2014;Sharp & Weaver, 2015;Sprey, 2009) and in the first issue of 2018 published two more articles that were clearly on LGBT issues (Allen & Mendez, 2018;Holman, 2018).…”
Section: Relative Percentages Of Lgbt-related Articlesmentioning
confidence: 74%
“…Between 2010 reported 86 articles published on LGBT-related issues out of 3,206 articles, a rate (2.68%) that was significantly lower than the rate in MFR between 2010 and 2017 (14/250, 5.6%), with an odds ratio of 2.15 (95% CI, 1.21 to 3.84, p = .01). We also observed that JFTR published at least 15 articles (of 208) between 2009 and 2017 that dealt with LGBT-family research issues, a rate of 7.2%, higher than MFR or the top seven family journals; those articles included 14 reviews or commentaries (Allen, 2016;Berkowitz, 2009;Cao, Mills-Koonce, Wood, & Fine, 2016;Chrisler, 2017;Cohen, 2011;Doucet & Lee, 2014;Few-Demo, Humble, Curran, & Lloyd, 2016;Fuller, 2017;Glennon, 2012;Goldberg, 2013;Lauer & Yodanis, 2010;McGuire, Catalpa, Lacey, & Kuvalanka, 2016;McGuire, Kuvalanka, Catalpa, & Toomey, 2016;Widiss, 2016; as well as one empirical paper (Connidis, 2012), not counting editorials for special issues (e.g., Oswald, 2016). In addition, JFTR also published four articles that tangentially mentioned LGBT issues (Few-Demo, 2014;Galvin & Braithwaite, 2014;Sharp & Weaver, 2015;Sprey, 2009) and in the first issue of 2018 published two more articles that were clearly on LGBT issues (Allen & Mendez, 2018;Holman, 2018).…”
Section: Relative Percentages Of Lgbt-related Articlesmentioning
confidence: 74%
“…Affective and behavioral forecasting, however, are not free of bias ( Warshaw and Davis, 1985 ; Wilson and Gilbert, 2005 ). To our knowledge, previous research on parental reactions toward their child’s coming out has been conducted entirely in retrospect; that is, parents or children were asked to remember their parents’ reactions ( Fuller, 2017 ; Ghosh, 2020 ). Interestingly, similar biases occur when people predict and remember emotional situations (e.g., tendencies to overestimate or overreport, respectively, emotional intensities; Levine et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imagining that one’s child could be LG should be easier when the child is still young and, probably, has not yet discovered or disclosed their sexual orientation. The affective and behavioral reaction items that participants completed upon this question were derived from the relevant literature cited above and recent reviews thereof ( Chrisler, 2017 ; Fuller, 2017 ; Ghosh, 2020 ). Furthermore, participants were asked about their general masculinity orientation and attitudes toward homosexuality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Είναι σημαντικό να διευκρινίσει κανείς ότι, επεκτείνοντας τη Θεωρία Διαπροσωπικής Αποδοχής και Απόρριψης, τα ερευνητικά δεδομένα που προκύπτουν αφορούν ολοένα και περισσότερες κοινωνικές ομάδες. Χαρακτηριστικό παράδειγμα αποτελεί η έρευνα για την αποδοχή και την απόρριψη σε ομοφυλόφιλα ζευγάρια (Fuller, 2017). Η μελέτη των Fuller και Rutter (2017) εστιάζει στον τρόπο με τον οποίο η αποδοχή ή απόρριψη των γονέων επηρεάζει τη σεξουαλική ταυτότητα και την ικανοποίηση από τις ενήλικες ερωτικές σχέσεις των ατόμων που ανήκουν στη ΛΟΑΤΚΙ κοινότητα.…”
Section: εμπειρικά δεδομένα και πρόσφατες έρευνεςunclassified